Pengaruh Progressive Muscle Relaxation terhadap Stres Mahasiswa Baru Jurusan Okupasi Terapi Poltekkes Surakarta - Nihayaturrohmah, Nihayaturrohmah; Kurnia, Rina (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Background.High stress levels during the first year of college can make students difficult to adapt and vulnerable to various social and psychological problems, which can decrease the GPA. To assist students in identifying and managing the stress they experience, it is necessary to recommend the application stress management training in educational programs (Chang et al.,2017). One of the stress management exercises that can be done is relaxation, one of the relaxation methods that can be used to reduce student stress levels is Progressive Muscle Relaxation. Objectives. This research was conducted to determine the effect progressive muscle relaxation the stress of new students in the Department of Occupational Therapy, Surakarta Polytechnic. Methods. The research conducted was a quantitative study with a pre-experimental type research design one group pretest-posttest. Student stress was calculated using the DASS instrument DASS 42, with the inclusion criteria of students who get a score of 15-18 on examination using DASS 42, are willing to get 12 interventions, and are not currently getting other interventions when they are sampled. The sample of the study was 30 students, and the sampling technique used purposive sampling.Data analysis used paired t-test technique, using an interval data scale. Result. Based on the characteristics of the research sample: the total number of respondents is 30 respondents. The number of female respondents was higher with 26 respondents. The age of respondents who took part in this study was 17-22 years old. The highest age distribution of respondents was at the age of 18 with a total of 20 respondents. Results pretest DASS 42 average scores 21.37. Resultposttestaverage 14.47. The total difference in the average value pretest and value posttest was 6.63. The results of data analysis using the paired t-test technique, p-value0.000 (p<0.05). Conclusion. These results indicate if the interventionProgressive Muscle Relaxation affects the stress of new students in the Department of Occupational Therapy, Surakarta Polytechnic. Keywords : Progressive MuscleRelaxation, New Student Stress